“BACK TO THE ELEMENTS”? POSTMODERNITY’S COLLAPSE OF ONTOLOGICAL CATEGORIES - Tupan, Maria-Ana (International Journal of Research -GRANTHAALAYAH, 2022)
Although the posthumanist tag is applied to the society where men and machines compete for power, the mutation earning this name was the one that affected the perception of man’s identity through the collapse of ontological categories. Human nature changed as the historical self was replaced by deconstructionists with the instance saying “I”, man’s cognition was redefined as biological epistemology by Maturana and Varela (1972), quantum physics relegated relations of causation to invisible and unpredictable process at the subatomic level, phases of civilization made room for temporary plateaus generated by signifying particles within the eternal flow of things and energy Deleuze and Guattari (1980). What used to be perceived as reality has become an amorphous mixture of elements, in which bodies are no longer discrete entites but processes, emerging forms of life. If the Deleuzian “becoming animal” of 1980 stirred anxiety around the human body made into a site of various inscriptions and identities, The Shape of Water (2018), a novel written by Guillermo del Toro and Daniel Kraus, the homonymous movie (2017) directed by the former, or Robert Bolesto’s screenplay of the Polish movie The Lure (2015) have recently provided the companion pieces of elementary nature “becoming human” across the human/ animal divide The quantum picture of a world reduced to a flux of matter and energy in A Thousand Plateaus by Gilles Deleuze and Félix Guattari had somehow prepared the ground for this posthuman reversal of the Renaissance worldpicture with man at the top of creation. The process, however, had already started some decades before. We are moving back in time locating its origin in the rise of object-oriented philosophy.